(Zoonymic Phrasemes Denoting Time in Macedonian Language - Велјановска, Катерина; Мирчевска-Бошева, Биљана (Poznańskie Studia Slawistyczne, 2021)
Тhis article analyses Macedonian phrasemes with zoonymic component denoting time. Zoonyms mainly came from surrounding environment which was expected having in mind the fact that man often reaches for something that is well known to him in an attempt to understand something far and abstract, such as the category of time. What distinguishes the analyzed units from the rest of the phraseological material with zoonymic components is their relative neutrality, bearing in mind that in general the zoonymic phrases are negatively colored. Such neutrality is due to their semantics, as well as to the fact that they show the characteristics and animals behavior as they are in reality